THE MAKING OF A NEW WORLD ECONOMIC ORDER IN THE 21ST CENTURY - TOMA SORIN-GEORGE (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
After the end of the Second World War, two opposing economic systems began to dominate the world economy: Western capitalism and Eastern communism. They were not only in an economic competition but also in a political, social and military competition. This bipolarity lasted until the Fall of the Berlin Wall when the liberal capitalism finally triumphed. On the one hand, the last decades were characterized by the rapid expansion of the economic globalization all over the world and the preservation of the long domination of the American economic superpower. On the other hand, the emergence and development of the BRICS (Brazil, Russia, India, China, South Africa) organization constitute an attempt to counterbalance the global institutions dominated by the Western countries. The paper aims to present and briefly analyse the gradual change of the world economic order in the beginning of the 21st century. To attain the goal of the paper, the author utilized a qualitative research method. To attain the goal of the paper, the author utilized a qualitative research method. The results of the study show that the old economic order that has governed the world economy since 1944 has been significantly deteriorated, especially in the last decades. This is why a new and more equitable economic order which should promote multilateralism is needed at the global scale.